Erosion–Seepage System (ESS) for Flow-Induced Soil Erosion Rate with Seepage - Yuhuan Zhang; Lin Cui; Dong-Sheng Jeng; Zheng Wang; Hualing Zhai (Journal of Marine Science and Engineering)
Critical shear stress and erosion rate are two key factors for the prediction of the incipient motion of sediment and the transport of sediment. Seabed seepage can significantly alter the pore pressure gradient within the soil and the hydrodynamics around the surface of the seabed, further affecting erosion processes. Previous studies attempted to theoretically clarify the effect of the seepage force on sediment incipient motion. In this study, a newly designed erosion–seepage system (ESS) that considers the effect of seepage under steady or oscillatory flow is used to simulate the erosion process. Through the designed ESS, the erosion height per unit time was measured directly on the Yellow River sand, and the upward seepage force was applied at the bottom of the soil sample in the process. Then, the relationship between the erosion rate and seepage was established.The experimental results show that upward seepage reduces the critical shear stress of the sand bed and increases the erosion rate of the soils under both steady flow and oscillatory flow conditions. The erosion coefficients in the erosion models decrease with increasing seepage gradient. The effect of seepage on erosion is more obvious when the flow velocity of the steady stream is large, while the effect of seepage on erosion is relatively small under the oscillatory state with a shorter period. However, when violent erosion of soil samples occurs, seepage under both flow conditions greatly increases the erosion rate.